MY SAY: Why is unity so hard to forge? - Abd Razak, Dzulkifli (2009)
Any hint of a merger or possible "unity talk" will invariably invite a variety of responses. More so because unity is Malaysia's mantra, well embossed on the nation's coat of arms: Bersekutu Bertambah Mutu, though not much attention is given to it. Today, the choice seems to be the more trendy Rukunegara or a myriad of other catchy slogans. So is this why unity is so hard to forge? Perhaps. In essence, unity has lost its true meaning as it has become more of a description of convenience for whatever exigencies: political, economic and social. All this excitement about forming a unity government is like the durianinspired muhibbah gatherings — such meetings have become seasonal. As the durian season becomes more erratic, so have the muhibbah gatherings — now they are almost unheard of. After a while, people become more sceptical and give unity a bad name. Increasingly, many would prefer to enjoy durians by themselves, without having to strike up small conversation for the sake of unity.